2013
DOI: 10.1186/2251-6581-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the avoidable burden of certain modifiable risk factors in osteoporotic hip fracture using Generalized Impact Fraction (GIF) model in Iran

Abstract: BackgroundsThe number of hip fractures, the most common complication of osteoporosis, has increased rapidly over the past decades. The goal of this study is to estimate the avoidable burden of certain modifiable risk factor of the condition using the Generalized Impact Fraction (GIF) model, which has been suggested and used by epidemiologists to overcome the drawbacks associated with the use of Attributable Fraction index. In addition to preventing a risk factor or the avoidable fraction of burden, this index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Considering the patients with osteoporosis, exercise is associated with a decreased risk of hip fractures [ 8 , 9 ]. Compared to a weight loss diet alone, diet related exercise or exercise and resistance training brings a relevant and important reduction in body fat and enhanced preservation of body lean mass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the patients with osteoporosis, exercise is associated with a decreased risk of hip fractures [ 8 , 9 ]. Compared to a weight loss diet alone, diet related exercise or exercise and resistance training brings a relevant and important reduction in body fat and enhanced preservation of body lean mass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Middle East, the problem of osteoporosis will soon be of greater importance considering the steady growth of the ageing population ((Maalouf et al 2007 ); IOF 2011a , 2012 ). Iran accounts for 0.85% of the global burden of hip fractures and 12.4% of the burden of hip fractures in the Middle East (Soveid et al 2005 ; Moayyeri et al 2006 ; Ahmadi-Abhari et al 2007 ; Beyranvand & Mohammadi 2009 ; Shahnazari et al 2013 ). Furthermore, hypovitaminosis D is highly prevalent in Middle Eastern countries and might be a strong contributing factor for osteoporosis (Gannage-Yared et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found four papers published on the burden of osteoporosis and osteoporotic fractures [5,10,16,19]. In 2001, a study was conducted to estimate the burden of osteoporosis in Iran, considering the fractures of the hip, spine, and forearm as the most common sites of fractures in older ages.…”
Section: The Burden Of Osteoporotic Fractures In Iranmentioning
confidence: 99%
“…Considering the burden of hip fracture, Shahnazari et al estimated the preventable burden of the known modifiable risk factor of osteoporotic hip fractures in Iran, using the Generalized Impact Fraction model [16]. They considered different scenarios showed that the highest impact in reducing the prevalence of osteoporotic hip fractures could be achieved by reducing the prevalence of low vitamin D, low physical activity, and low vitamin D and calcium intake, respectively.…”
Section: The Burden Of Osteoporotic Fractures In Iranmentioning
confidence: 99%
See 1 more Smart Citation